Social factors affecting the reduction of drug addicts\' relapse - Abolghasem Norouzi; Shapour Behan; Mohammad Ali Chitsaz (مجله علوم روانشناختی)
Background: Most studies in the field of addiction have focused on indicators affecting addiction, and a few studies have focused on the effect of social factors on drug relapse. Therefore, due to the multidimensional nature of the tendency to drug use, the study of drug reorientation through biological, social, cultural, and psychological factors is a basic necessity. Aims: This study aimed to investigate the social factors affecting the reduction of drug addicts' relapse. Methods: The research method was descriptive and correlational. The statistical population of this study consisted of all young people in the age range of 15 to 30 years old in Izeh city in 2024, which according to the report of the Drug Control Organization of Izeh city, is 3200 people. The sample consisted of 345 young drug users who were referred to addiction treatment camps in Izeh City and were selected by convenience sampling. To collect the research data, the researcher-made social learning, social support, and social participation questionnaires and the craving of Salehi Fadardi et al. (2010) were collected. To analyze the research data, SPSS.26 software was used using Pearson correlation coefficient and multivariate regression using simultaneous method. Results: The results of the Pearson correlation coefficient showed that there is a negative and significant relationship between social learning, social support, and social participation with craving (P< 0.05). The results of multivariate regression showed that social support (35%), social participation (62%), and social learning (13%) explained the variance of drug relapse temptation in young people, respectively. Conclusion: The results show that people who are more likely to reuse drugs have lower levels of support, participation, and social learning. Therefore, it is recommended to pay attention to these variables and develop educational programs based on these variables to reduce drug reuse in users.